Does carbohydrate intake during endurance running improve performance? A critical review - Wilson, P. B. (The Journal of Strength and Conditioning Research, 2016)
Previous review articles assessing the effects of carbohydrate ingestion during prolonged exercise have not focused on running. Given the popularity of distance running and the widespread use of carbohydrate supplements, this article reviewed the evidence for carbohydrate ingestion during endurance running. The criteria for inclusion were (a) experimental studies reported in English language including a performance task, (b) moderate-to-high intensity exercise >60 minutes (intermittent excluded), and (c) carbohydrate ingestion (mouth rinsing excluded). Thirty studies were identified with 76 women and 505 men. Thirteen of the 17 studies comparing a carbohydrate beverage(s) with water or a placebo found a between-condition performance benefit with carbohydrate, although heterogeneity in protocols precludes clear generalizations about the expected effect sizes. Additional evidence suggests that (a) performance benefits are most likely to occur during events >2 hours, although several studies showed benefits for tasks lasting 90-120 minutes; (b) consuming carbohydrate beverages above ad libitum levels increases gastrointestinal discomfort without improving performance; (c) carbohydrate gels do not influence performance for events lasting 16-21 km; and (d) multiple saccharides may benefit events >2 hours if intake is =1.3 g/min Given that most participants were fasted young men, inferences regarding women, adolescents, older runners, and those competing in fed conditions are hampered. Future studies should address these limitations to further elucidate the role of carbohydrate ingestion during endurance running.